2020
DOI: 10.1155/2020/6785835
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Resolution of Drug-Related Problems among Childhood Cancer Patients in Ethiopia

Abstract: Background. Even though medications play a major role in the cure, palliation, and inhibition of disease, they also expose patients to drug-related problems. Drug-related problems are frequent and may result in reduced quality of life, morbidity, and mortality.Objectives.e study was aimed to identify, characterize, and resolve drug-related problems in the Pediatric Hematology/ Oncology ward of Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia. Methods. A prospective observational study was conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 31 publications
(36 reference statements)
3
39
2
2
Order By: Relevance
“…Similar findings were reported previously in 2011in one of the national hospitals where dosage or frequency of medication followed by addition of drugs to therapy represented the most common issue (32.4% and 19.5% respectively) 26 Globally, as per a study conducted at a multi-specialty teaching hospital, the suboptimal dosing was the most common DRP, 27 Most of the common improper drug selection was related to antibiotics, which is in line with a previous study where anti-infective was the most common class of drug for DRPs. 28 In the current study, the overall percentage of DRPs was 8.5% of the total clinical pharmaceutical sheets reviewed, which was less than that of the internal medicine ward probably due to low number of drugs dispensed pre and post-operatively. This percentage could be acceptable compared to a few studies done in developed countries that showed that the values reported in a German orthopaedic and accident surgery ward using the APS-Doc coding and Swiss cardiovascular surgery ward using a simplified PCNE classification system were 2.6% 29 And 1.7%, 30 respectively.…”
Section: Drug Related Problems In Clinical Pharmacist Sheets (Cps) Ov...contrasting
confidence: 53%
“…Similar findings were reported previously in 2011in one of the national hospitals where dosage or frequency of medication followed by addition of drugs to therapy represented the most common issue (32.4% and 19.5% respectively) 26 Globally, as per a study conducted at a multi-specialty teaching hospital, the suboptimal dosing was the most common DRP, 27 Most of the common improper drug selection was related to antibiotics, which is in line with a previous study where anti-infective was the most common class of drug for DRPs. 28 In the current study, the overall percentage of DRPs was 8.5% of the total clinical pharmaceutical sheets reviewed, which was less than that of the internal medicine ward probably due to low number of drugs dispensed pre and post-operatively. This percentage could be acceptable compared to a few studies done in developed countries that showed that the values reported in a German orthopaedic and accident surgery ward using the APS-Doc coding and Swiss cardiovascular surgery ward using a simplified PCNE classification system were 2.6% 29 And 1.7%, 30 respectively.…”
Section: Drug Related Problems In Clinical Pharmacist Sheets (Cps) Ov...contrasting
confidence: 53%
“…(2020), onde o percentual de aceitação das IF realizadas foi de 92% e as intervenções mais efetuadas pelos farmacêuticos foram os ajustes de dosagens, inclusão de terapia adicional e a não-adesão ao tratamento. Esse estudo foi feito entre pacientes com câncer infantil da Etiópia, onde os autores relatam que tratar esse tipo de doença ainda é um dos mais complexos desafios enfrentados pela medicina, pois, está associado a muitos PRM, como por exemplo, os efeitos adversos, EM, interações medicamentosas e não adesão ao tratamento, fatores estes que foram identificados no estudo em questão (19).…”
Section: Resultsunclassified
“…2 Thus, drug-related problems (DRP) are common among pediatric cancer patients and clinical pharmacy plays an essential role detecting and resolving them. 3 We read the article by Diop et al 4 that evaluated prescriptions of anti-infective drugs and potential drug interactions in a pediatric oncology-hematology unit. They analyzed 195 prescriptions; 6.6% of them contained at least one over-dosed drug and 26.7% contained at least one under-dosed drug.…”
Section: Clinical Pharmacy Services In Pediatric Hematology-oncology:mentioning
confidence: 99%
“…2 Thus, drug-related problems (DRP) are common among pediatric cancer patients and clinical pharmacy plays an essential role detecting and resolving them. 3…”
mentioning
confidence: 99%